Peptides Derived from Soybean β-Conglycinin Induce the Migration of Human Peripheral Polymorphonuclear Leukocytes - Itagaki, Fumio; Kishimoto, Seishi; Watanabe, Machiko; Fujii, Norihiko; Yasuno, Nobuhiro; Nagashima, Kazuki; Oka, Saori; Yamashita, Atsushi (Biological & pharmaceutical bulletin, 2023)
Food-derived peptides have various biological activities. When food proteins are ingested orally, they are digested into peptides by endogenous digestive enzymes and absorbed by the immune cell-rich intestinal tract. However, little is known about the effects of food-derived peptides on the motility of human immune cells. In this study, we aimed to understand the effects of peptides derived from a soybean protein β-conglycinin on the motility of human peripheral polymorphonuclear leukocytes. We illustrated that MITL and MITLAIPVNKPGR, produced by digestion using in-vivo enzymes (trypsin and pancreatic elastase) of β-conglycinin, induces the migration of dibutyryl cAMP (Bt2 cAMP)-differentiated human promyelocytic leukemia 60 (HL-60) cells and human polymorphonuclear leukocytes in a dose- and time-dependent manner. This migration was more pronounced in Bt2 cAMP-differentiated HL-60 cells; mRNA expression of formyl peptide receptor (FPR) 1 increased significantly than in all-trans-retinoic acid (ATRA)-differentiated HL-60 cells. This migration was inhibited by tert-butoxycarbonyl (Boc)-MLP, an inhibitor of FPR, and by pretreatment with pertussis toxin (PTX). However, the effect was weak when treated with WRW4, a selective inhibitor of the FPR2. We then demonstrated that MITLAIPVNKPGR induced intracellular calcium responses in human polymorphonuclear leukocytes and Bt2 cAMP-HL60 cells. Furthermore, pre-treatment by fMLP desensitized the calcium response of MITLAIPVNKPGR in these cells. From the above, MITLAIPVNKPGR and MITL derived from soybean β-conglycinin induced polymorphonuclear leukocyte migration via the FPR1-dependent mechanism. We found chemotactic peptides to human polymorphonuclear leukocytes, which are the endogenous enzyme digests of soybean protein.